Single-staged surgical approach in congenital diaphragmatic hernia associated with esophageal atresia - Zahn, Katrin; Nankeng, Sabrina; Schaible, Thomas; Wessel, Lucas; Hagl, Cornelia Irene (Journal of pediatric surgery, 2015)
Background: The coexistence of congenital diaphragmatic hernia (CDH) with esophageal atresia (EA) has only been reported occasionally in literature. Series of patients from a single institution with comparison of different postnatal therapeutic approaches have not been reported. We describe our management in this unique cohort of patients and discuss the procedures that can lead to successful outcomes in this association of congenital anomalies. Methods: The surgical approaches and outcome of six neonates with CDH associated with EA and distal tracheo-esophageal fistula (TEF) are discussed. Results: Five newborns were treated surgically, while one patient with trisomy 18 only received palliative treatment. In four patients TEF was ligated during laparotomy for CDH repair. Secondary surgery was performed for correction of EA via thoracotomy after 4-6weeks (primary anastomosis in two patients, Foker’s-technique in one patient, one patient deceased prior to secondary surgery). All three surviving patients required fundoplication due to severe gastro-esophageal reflux during the first year of life. Two patients also required dilatation for anastomotic stricture. In one preterm infant correction of both malformations was accomplished during one surgical intervention. The herniated organs were eventrated and temporarily placed into a silastic bag to allow a mediastinal shift to the left. Thus a continuous ventilation of the right lung with minimal compression and sufficient oxygenation was possible during esophageal repair via a right-sided thoracotomy and extrapleural approach. No further surgery was required so far. Conclusions: Definitive surgical correction in newborns with CDH and EA was so far accomplished with multiple surgical interventions. Ligation of TEF via an abdominal approach with repair of CDH followed by delayed repair of EA is prone to stenosis and gastro-esophageal reflux due to loss of esophageal length. With a new combination of established surgical methods a single-staged correction of both malformations is possible. This new approach might help to preserve sufficient length of esophagus to accomplish primary anastomosis without tension and therefore avoid long-term morbidity and repetitive surgeries.
Gesehen am 11.12.2018
Available online 28 April 2015